Production of baculovirus defective interfering particles during serial passage is delayed by removing transposon target sites in fp25k - Giri, Lopamudra (Society for General Microbiology, 2012)
Accumulation of baculovirus defective interfering particle (DIP) and few polyhedra (FP) mutants is a major limitation to continuous large-scale baculovirus production in insect-cell culture. Although overcoming these mutations would result in a cheaper platform for producing baculovirus biopesticides, little is known regarding the mechanism of FP and DIP formation. This issue was addressed by comparing DIP production of wild-type (WT) Autographa californica multiple nucleopolyhedrovirus (AcMNPV) with that of a recombinant AcMNPV (denoted Ac-FPm) containing a modified fp25k gene with altered transposon insertion sites that prevented transposon-mediated production of the FP phenotype. In addition to a reduction in the incidence of the FP phenotype, DIP formation was delayed on passaging of Ac-FPm compared with WT AcMNPV. Specifically, the yield of DIP DNA in Ac-FPm was significantly lower than in WT AcMNPV up to passage 16, thereby demonstrating that modifying the transposon insertion sites increases the genomic stability of AcMNPV. A critical component of this investigation was the optimization of a systematic method based on the use of pulsed-field gel electrophoresis (PFGE) to characterize extracellular virus DNA. Specifically, PFGE was used to detect defective genomes, determine defective genome sizes and quantify the amount of defective genome within a heterogeneous genome population of passaged virus.